Global Africa : into the twenty-first century - Hodgson, Dorothy Louise; Byfield, Judith A. (Judith Ann-Marie) (Oakland, California : University of California Press, 2017)
"Global Africa will complicate conventional views of Africa as a place of violence, despair and victimhood--a place and space that other people, states, and organizations act on and steal from. Instead, they aim to document some of the significant global connections, circulations, and contributions that African people, ideas, and goods have made in the world--not just in the United States, but in South Asia, Latin America, Europe, and elsewhere. They will showcase new framings of Africa, but will not romanticize the conditions and circumstances in which too many people on the continent currently live. The essays in this volume will amplify those voices that offer complex and insightful explanations, strategies for solutions, and inspiration for the future."--Provided by publisher.
Entangled histories -- Power and its challenges -- Circulations of communities and cultures -- Science, technology, and health -- Africa in the world today.
Includes bibliographical references and index.
Keywords: Globalization -- Africa -- 21st century; National characteristics, African; Africa -- Economic conditions -- 21st century; Africa -- Social conditions -- 21st century; Africa -- Politics and government -- 21st century; Africa -- Foreign relations -- 21st century